Enforcement matters: The effective regulation of labour. (14th September 2018) - KANBUR, Ravi; RONCONI, Lucas
Abstract: The distinction between de jure and de facto regulation is well understood in theory, but has rarely been applied to cross‐country empirical work on the impact of labour regulation on labour market outcomes for lack of data. Policy debate has been based on measures of stringency of law, suggesting a negative correlation between labour regulation and labour market outcomes. This article provides new cross‐country measures of labour law enforcement and evidence of a negative correlation between stringency and intensity of enforcement. Previous results concerning the consequences of labour regulation and the legal origins theory no longer hold when a measure of effective labour regulation is used.